The Influence of Job Mindfulness on Emotional Exhaustion Through Psychological Distress and Workplace Bullying as Mediation Variables - Syarifah Mulya Safitri M Sahab; Erni Febrina Harahap; Fivi Anggraini (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to clearly prove the effect of job mindfulness on emotional exhaustion through psychological distress and workplace bullying as mediating variables in employees of Bank Nagari Main Branch, Padang. In the research, 141 people were selected using the census method. Data collection is carried out by distributing questionnaires directly to employees who fulfill the specified selection procedures. The data analysis method used is path analysis which is processed using Partial Least Square (PLS). Job mindfulness and psychological distress have no effect on the emotional exhaustion felt by employees of Bank Nagari Padang Main Branch, while workplace bullying has a positive effect on the emotional exhaustion felt by employees of Bank Nagari Main Branch Padang. In the hypothesis testing stage, it was also found that Job Mindfulness had a negative effect on the psychological distress felt by Bank Nagari Main Branch employees. Apart from that, Job Mindfulness has a negative effect on workplace bullying felt by employees in the Bank Nagari Padang Main Branch environment. In the indirect influence testing stage, it was found that psychological distress did not mediate the relationship between job mindfulness and emotional exhaustion felt by employees of Bank Nagari Main Branch, Padang, whereas in the second indirect influence test, it was found that Workplace bullying was able to mediate the relationship between job mindfulness and emotional exhaustion in Bank Nagari Branch employees at Padang main branch.